Gender and Power in Shrew-Taming Narratives, 1500-1700
IX, 236 p.
Keywords: Explores dramatic, narrative and polemical versions of the 'taming of the shrew' story, from the Middle Ages to the Restoration, in light of recent historical work on the position of early modern women in society. Its essays address shrew narratives as an extended cultural dialogue debating issues of gender and sexual politics.